2020
DOI: 10.1021/acsapm.9b01177
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Deposition of Functional Porous Polymer Membranes

Abstract: The fabrication of porous polymer membranes is currently dominated by solution-phase processing techniques. We recently developed a versatile solventless method to deposit porous polymer membranes. In this paper, we will review the mechanism that governs the fabrication process, the advantages and capabilities of the technique, and potential applications for these membranes. In the fabrication process, low substrate temperatures are used to transition the monomer vapor into solid microstructures which are then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 66 publications
(110 reference statements)
1
23
0
Order By: Relevance
“…Porous polymer coatings have applications in drug delivery devices, , biosensors, , and separations. , Porous polymers are commonly synthesized using liquid-phase processing techniques such as phase inversion, , cryopolymerization, , and solvent casting and particulate leaching. , The presence of solvents in these techniques can cause swelling and degradation of substrates and also limit the conformality of the coatings onto curved surfaces . We recently developed a solvent-free and substrate-independent method to grow porous polymers from vapor-phase precursors. The all dry and bottom-up nature of our fabrication process eliminates solubility requirements and surface tension issues such as dewetting and clogging and provides a high degree of control over chemical composition and thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Porous polymer coatings have applications in drug delivery devices, , biosensors, , and separations. , Porous polymers are commonly synthesized using liquid-phase processing techniques such as phase inversion, , cryopolymerization, , and solvent casting and particulate leaching. , The presence of solvents in these techniques can cause swelling and degradation of substrates and also limit the conformality of the coatings onto curved surfaces . We recently developed a solvent-free and substrate-independent method to grow porous polymers from vapor-phase precursors. The all dry and bottom-up nature of our fabrication process eliminates solubility requirements and surface tension issues such as dewetting and clogging and provides a high degree of control over chemical composition and thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The annealing process helps control dissolution of the sponge coating through partial conversion of MAA to MAN but does not prevent dissolution since the sample is not covalently crosslinked. The P­(MAA- co -MAN) coating can be permanently crosslinked by exposure to strongly nucleophilic 1,3-diaminopropane vapors. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The P(MAA-co-MAN) coating can be permanently crosslinked by exposure to strongly nucleophilic 1,3-diaminopropane vapors. 19,33,47 For applications such as oil/water separation 48 and wound dressings, 33,49 it is important for the porous coating to have good adhesion to the underlying substrate. We have previously shown that we can increase the adhesion of the pillared coatings shown in Figure 1a to underlying substrates through the incorporation of the epoxide-containing glycidyl methacrylate (GMA) monomer into the fabrication process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas-phase monomer and peroxide initiator molecules flow into a vacuum chamber with fixed pressure where a hot wire filament activates the initiator and monomer adsorbs to the surfaces of samples placed on a relatively cool stage. The iCVD technique characteristically applies conformal polymer coatings on substrates of arbitrary shape and has been extensively used for coating non-planar materials including nanopores, [53][54][55] membranes, [56][57][58] scaffolds, [59][60][61] and fabrics. [62][63][64] The technique is particularly useful for preparing polymer coatings that are difficult to process in solution due to solubility or surface energy constraints, such as fluoropolymers.…”
Section: Introductionmentioning
confidence: 99%